2010
DOI: 10.1007/s11769-010-0434-0
|View full text |Cite
|
Sign up to set email alerts
|

Change in fresh snow density in Tianshan Mountains, China

Abstract: The fresh snow density was observed with snow analyzer (Snow Fork) at Tianshan Station for Snowcover and Avalanche Research, Chinese Academy of Sciences from February 21 to March 5, 2009. Results show that fresh snow density increases from the 5th h to the 291st h after the snowfall, with an average rate of increase of 4.0×10 -4 g/(cm 3 ·h) (R 2 = 0.943). Analysis shows that fresh snow density is negatively correlated with the compaction rate of fresh snow (R 2 = -0.960). Inversely, it is positively correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Chen et al . () observed that the fresh snow density in the Tianshan Mountain region increases drastically with the time with a quadruple increase in about 10 days. The weight of the upper layers of snow acts to densify the lower part of the deposit (Judson and Doesken, ).…”
Section: Summary and Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Chen et al . () observed that the fresh snow density in the Tianshan Mountain region increases drastically with the time with a quadruple increase in about 10 days. The weight of the upper layers of snow acts to densify the lower part of the deposit (Judson and Doesken, ).…”
Section: Summary and Discussionmentioning
confidence: 98%
“…Based on observations at Colorado, Judson and Doesken (2000) showed that the snow density declines largely with the temperature drop. Chen et al (2011) observed that the fresh snow density in the Tianshan Mountain region increases drastically with the time with a quadruple increase in about 10 days. The weight of the upper layers of snow acts to densify the lower part of the deposit (Judson and Doesken, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our main innovation is to separate the observed negative correlation between depth and density over short timescales from their positive correlation at longer timescales. The importance of different governing processes at separate timescales has been observed in field studies of bulk densities (e.g., Chen et al, 2011). Incorporating behavior at distinct timescales into our new model provides more realistic daily time series of bulk density.…”
Section: Introductionmentioning
confidence: 85%
“…natural seasonality and regional temperature changes on snow densities, which could also modify passive microwave SWE estimates over the course of our time series, and thus are part of the trends that we present as changes in SWE in this study (Judson and Doesken, 2000;Chen et al, 2011;Dai et al, 2012). The impact of seasonal oscillations in snow density is somewhat mitigated by removing the seasonal cycle from our data before trend fitting, as some of the seasonality in SWE estimates will be driven by changes in snow density.…”
Section: Data Caveatsmentioning
confidence: 92%